Renal Autotransplantation in Metachronous Solitary Contralateral Ureteral Metastasis from Renal Cell Carcinoma: A Case Report - Bretterbauer, Katharina; Drerup, Martin; Heidler, Stefan; Lösch, Georg; Albrecht, Walter (Urology Journal, 2017)
Ureteral metastasis of renal cell carcinoma (RCC) is rare and usually confined to the ipsilateral ureter. In literature, about 50 cases have been reported so far. Of these, only 14 metastasized metachronously to the contralateral ureter. A seventy-one-year-old man was hospitalized with recurrent painless severe haematuria. Seven years previously, he had undergone radical nephrectomy of the right kidney due to a clearcell renal cell carcinoma (cRCC), Fuhrman grad 2. Intravenous urography and a retrograde ureterogram revealed a filling defect (25 mm) in the left distal ureter, which we expected to be an urothelial carcinoma. Biopsy was not possible, due to ureteral stricture. Diagnostic workup revealed no other sites of metastasis. To preserve kidney function and quality of life we refrained from performing nephroureterectomy and opted for an autotransplantation of the solitary left kidney with ureteral reimplantation in the bladder. We resected the ureter and histopathologicial examination showed a metastasis of cRCC, Fuhrman grade 2. Postoperatively, the patient developed an acute postrenal failure, hence a nephrostomy and a bladder catherization were performed. After this, the patient improved significantly and the drains could be removed. Currently the patient is free of complaints. The residual and contralateral ureter is a potential metastatic site after RCC. Autotransplantation is an option for surgical treatment.